2022
DOI: 10.3389/fcvm.2022.810262
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Comorbidity of Hypertension and Renal Cell Carcinoma in the Cardio-Oncologic Era and Treatment for Tumor-Induced Hypertension

Abstract: Advances in tumor diagnosis and treatment, especially the use of targeted therapies, have remarkably improved the survival rate of patients with renal cell carcinoma (RCC), accompanied by higher hypertension (HTN) incidence among patients with RCC, reflecting the coming of a cardio-oncologic era. Therefore, for patients with RCC and HTN simultaneously, finding risk factors for the comorbidity and giving better clinical treatment have been urgent problems. In this review, we thoroughly investigated risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 105 publications
1
11
0
Order By: Relevance
“…On the histological levels, losartan mitigated the vascular toxicity of tivozanib and showed a healthy opened aorta with improved layers. These findings are consistent with the recent recommendations of using angiotensin system inhibitors, including angiotensin-converting enzyme inhibitors (ACEs) and angiotensin-II type 1 receptor blockers (ARBs) as a therapy in the management of hypertension caused by VEGFR-TKIs including sorafenib, sunitinib, tivozanib [ 16 , 20 ]. Although RAAS is crucially involved in the pathogenesis of essential hypertension, there is an absence of evidence that RAAS contributes significantly to hypertension caused by VEGFR-TKI [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the histological levels, losartan mitigated the vascular toxicity of tivozanib and showed a healthy opened aorta with improved layers. These findings are consistent with the recent recommendations of using angiotensin system inhibitors, including angiotensin-converting enzyme inhibitors (ACEs) and angiotensin-II type 1 receptor blockers (ARBs) as a therapy in the management of hypertension caused by VEGFR-TKIs including sorafenib, sunitinib, tivozanib [ 16 , 20 ]. Although RAAS is crucially involved in the pathogenesis of essential hypertension, there is an absence of evidence that RAAS contributes significantly to hypertension caused by VEGFR-TKI [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…In cancer patients treated with tivozanib, clinical trials showed that around 45% of them suffered from hypertension as the most common adverse reaction, and 8% were reported with proteinuria [ 13 , 14 , 16 ]. Still, the causes of tivozanib-induced hypertension are not clearly identified.…”
Section: Discussionmentioning
confidence: 99%
“…7,45 Smoking has direct correlations with hypertension, which has frequently been recorded as an independent risk factor for RCC in a dose-dependent fashion, therefore, it is unsurprising that this variable was present in greater than two-thirds of our sample. 44,46 Alternatively, obesity, previously reported in 30% -40% of RCC diagnosis, was seen in nearly 60% of our cohort which may have contributed to an increased risk among our population and may warrant greater examination. 4,44,46 Despite lack of consistent evidence for type 2 diabetes as a risk factor, this condition was still seen in one-quarter of our patients, supporting the likelihood of a previously proposed interplay with other chronic comorbid conditions in the development of RCC.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, several factors are often overlooked when assessing both hypertension and CVD risk within cancer patient populations, such as advances in cancer and cardiovascular disease screening, increased public awareness and engagement with their own health, improved therapies and imaging techniques, prolonged survival post treatment and of most significance an escalating aging population could indicate we may be on the verge of an even larger expansion era for cardio-oncology and its treatment-related issues. 5,213…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…212 Furthermore, several factors are often overlooked when assessing both hypertension and CVD risk within cancer patient populations, such as advances in cancer and cardiovascular disease screening, increased public awareness and engagement with their own health, improved therapies and imaging techniques, prolonged survival post treatment and of most significance an escalating aging population could indicate we may be on the verge of an even larger expansion era for cardio-oncology and its treatment-related issues. 5,213 An overt deficiency of standardized cardiovascular risk assessment tools established and validated for use in patients with cancer and survivors highlights a significant deficit in care within this population. An explanation for this may be that most cardio-oncology and cancer patient trials include younger, typically low-risk populations and the application of CVD risk assessment/predictive tools may falsely underestimate cardiovascular risk and events which may not be reflective of real-world practice and therefore incorrectly guide treatment decisions.…”
Section: Hypertension As a Risk Factor For Cardiotoxicitymentioning
confidence: 99%